Aneuploidy and high S-phase as biomarkers of poor clinical outcome in poorly differentiated and anaplastic thyroid carcinoma - Pinto, António E. (2008)
This study aimed to investigate the prognostic influence of DNA flow cytometry and RAS gene mutations in patients with poorly differentiated (PDTC) and anaplastic thyroid carcinoma (ATC). The series consisted of 26 patients with PDTC and ATC, and a median follow-up of 10 months (range 1-138). DNA ploidy and S-phase fraction (SPF) were assessed by flow cytometry on frozen samples. RAS point mutations were detected using PCR techniques. Disease staging and tumour angioinvasion were included as prognostic parameters for survival analysis. Nineteen patients (73.1%) succumbed to the disease (median time 5 months; range 1-45). Eighteen tumours (69.2%) were classified as DNA aneuploid. Median SPF was 5.6% (range 1.9-23.1), which was used as a cut-off value to distinguish between low versus high cell proliferation. Three of 20 (15%) patients presented N-RAS gene mutations in codon 61. DNA aneuploidy was most frequently found in female patients (p=0.034). Kaplan-Meier and Cox regression analyses showed that only DNA aneuploidy (p=0.044 and p=0.055, respectively) and high SPF (p=0.001 and p=0.006, respectively) significantly correlated with worse survival. The results indicate that aneuploidy and high SPF are biomarkers of poor clinical outcome in PDTC and ATC, which may provide useful prognostic information with a potentially therapeutic impact in patient management.